Partisipasi Masyarakat dalam Pelaksanaan Program Hubungan Sekolah-Masyarakat di Sekolah Dasar - Agus Timan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This desciptive-correlational research was designed to describe community participation in the school-public relation programs. It collected data from elementary schools in Malang Municipality by using questionnaire and documentation, and then analyzed statistically by percentage, product moment correlation, and t-test. It was found out that community participation in the school-public relation programs was high, and that the programs were effective. The program effectiveness was related to the community participation. There were differences in the level of community participation and in the program effectiveness among the elementary schools.